Genetics and human skeletal variation - Weaver, Timothy (Henry Stewart Talks, 2015)
Quantifying human skeletal variation, Genetic & environmental basis of human skeletal variation, Observations about human genetic variation, Patterns of cranial variation vs. patterns of genetic variation, Evolutionary processes that shaped patterns of cranial variation, Humans in comparison with other taxa